Immunogenicity and safety of an investigational hepatitis B vaccine with a Toll-like receptor 9 agonist adjuvant (HBsAg-1018) compared with a licensed hepatitis B vaccine in patients with chronic kidney disease and type 2 diabetes mellitus. Issue 7 (11th February 2015) - Janssen, Julia M.; Heyward, William L.; Martin, J. Tyler; Janssen, Robert S.
Highlights Phase 3 trial of investigational hepatitis B vaccine in CKD and diabetes. HBsAg-1018 induced superior seroprotection to HBsAg-Eng. The safety profile of HBsAg-1018 was similar to that of HBsAg-Eng.